A bibliometric analysis of wildlife tourism research from 1991–2022 - Nasir, Tanveer; Raina, Danish Iqbal; Wani, Zishan Ahmad; Ridwan, Qamer; Hanief, Mohd; Pant, Shreekar; Rawat, Yashwant S. (Frontiers in Sustainable Tourism, 2024)
In the present study, a bibliometric analysis of 453 publications published between 1991 and 2022 was carried out in order to evaluate and analyze the existing academic literature, as well as to identify current research trends and hotspots on this topic. Three different sorts of bibliometric indicators: quantitative, qualitative, and structural, were analyzed. The results revealed a steady increase in publications on wildlife tourism since 1991, with the journal Tourism Management being the most prolific source of research articles. A total of 70 countries and territories have contributed to these research publications, with Australia having the highest number of research publications. Among the most cited authors, sources and countries, Ballantyne R, Tourism Management, and Australia top the list, respectively. It was observed that a total of 232 research collaborations have been made across different countries in wildlife tourism research, with the highest number of collaborations between Australia and the USA. A keyword frequency analysis revealed that terms such as conservation, wildlife tourism, management, ecotourism, and wildlife behavior were the most frequently used. The present study provides insights into the current state of research in SWT and highlights key contributors, collaborations, and research themes in the field. The findings can serve as a foundation for future research in wildlife tourism by identifying core research areas, potential collaborators, and impactful journals. The study can further contribute to the growing body of knowledge in the field and guide researchers in selecting suitable journals for publishing their research works.